2021
DOI: 10.1001/jamacardio.2020.7050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Systematic Echocardiographic Screening for Rheumatic Heart Disease in Nepalese Schoolchildren

Abstract: IMPORTANCEEchocardiographic screening allows for early detection of subclinical stages of rheumatic heart disease among children in endemic regions.OBJECTIVE To investigate the effectiveness of systematic echocardiographic screening in combination with secondary antibiotic prophylaxis on the prevalence of rheumatic heart disease.DESIGN, SETTING, AND PARTICIPANTS This cluster randomized clinical trial included students 9 to 16 years of age attending public and private schools in urban and rural areas of the Sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
(33 reference statements)
0
10
0
1
Order By: Relevance
“…Echocardiographic screening in combination with secondary antibiotic prophylaxis in children with evidence of latent rheumatic heart disease is currently investigated to reduce its prevalence in endemic regions. 91 In patients with established rheumatic heart disease, secondary long-term prophylaxis against rheumatic fever is recommended: benzathine benzyl penicillin 1.2 MUI every 3 to 4 weeks over 10 years. Lifelong prophylaxis should be considered in high-risk patients according to the severity of VHD and exposure to group A Streptococcus.…”
Section: Prophylaxis For Rheumatic Fevermentioning
confidence: 99%
“…Echocardiographic screening in combination with secondary antibiotic prophylaxis in children with evidence of latent rheumatic heart disease is currently investigated to reduce its prevalence in endemic regions. 91 In patients with established rheumatic heart disease, secondary long-term prophylaxis against rheumatic fever is recommended: benzathine benzyl penicillin 1.2 MUI every 3 to 4 weeks over 10 years. Lifelong prophylaxis should be considered in high-risk patients according to the severity of VHD and exposure to group A Streptococcus.…”
Section: Prophylaxis For Rheumatic Fevermentioning
confidence: 99%
“…Nevertheless, we have demonstrated that a rapid single-view screening protocol can be performed in just over one-minute with a high degree of accuracy. School-based screening programs appear to be cost effective and reduce the risk of RHD overtime [5,18,19]. As new evidence emerges and technology improves, increased funding for RHD is needed to meaningfully reduce the global burden of disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic screening has been advocated as an effective screening measure for the early detection of latent RHD for which a standard WHF criteria for echocardiographic diagnosis of rheumatic heart disease was developed in 2012 [ 12 ]. School-based echocardiographic screening in combination with secondary antibiotic prophylaxis in children with evidence of latent rheumatic heart disease was found to be an effective strategy to reduce the prevalence of definite or borderline rheumatic heart disease in endemic regions [ 13 ]. For advanced cases, appropriate cardiac care services for medical and surgical management are required which are not easily accessible in all areas like Nepal.…”
Section: Discussionmentioning
confidence: 99%